Trace elements in eggs of common eiders (Somateria mollissima) breeding in Nova Scotia, Canada. Issue 1 (15th November 2015) - Pratte, Isabeau; Tomlik, Molly D.; Betsch, Taylor A.; Braune, Birgit M.; Milton, G. Randy; Mallory, Mark L.
Abstract: We provide the first report on trace element concentrations in eggs of common eiders ( Somateria mollissima ), a coastal benthic foraging sea duck, from Nova Scotia, Canada, and compare those to known values from this species elsewhere. Most trace elements of toxicological concern (Hg, Se, Cd, Cu, Zn) were lower in eider eggs from Nova Scotia than from eider eggs collected farther north in Canada, although As was elevated. Our data provide strong support for a pattern of increasing Hg at higher latitudes for this species. Highlights: Common eider eggs were sampled in Nova Scotia, Canada. Most trace elements of toxicological concern were in lower concentrations than found in the Canadian Arctic. Declines in local eiders are not likely related to toxicological stress.